Navigating the Halal Traceability in Global Supply Chains: Deep Insights from Small-Scale Food Producers - Aan Zulyanto; Dharma Setiawan (Indonesian Development Economics and Localities, 2025)
The global halal food industry has experienced rapid expansion, driven by growing Muslim populations and increasing consumer demand for certified halal products. Despite this growth, small-scale food producers continue to face significant challenges in implementing effective halal traceability systems within complex global supply chains. This study investigates the traceability challenges encountered by small-scale food producers in Indonesia, with broader implications for the global halal food sector. Employing a qualitative research design, data were collected through in-depth semi-structured interviews with fifteen small-scale halal food producers in Bengkulu Province, Indonesia. Thematic analysis was applied to identify key patterns and themes from the data. The findings reveal four major themes: (1) systemic traceability challenges related to documentation and supply chain visibility; (2) difficulties in accessing and maintaining halal certification; (3) limited adoption of digital technologies for traceability management; and (4) trust and integrity issues across the supply chain. This study concludes that targeted policy interventions, technology capacity-building programs, and streamlined certification processes are essential to support small-scale producers in achieving robust halal traceability. The findings contribute to the growing body of halal supply chain literature and offer practical implications for industry stakeholders and policymakers.